2017
DOI: 10.1575/1912/9160
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of uranium from seawater : design and testing of a symbiotic system

Abstract: Seawater is estimated to contain 4.5 billion tonnes of uranium, approximately 1000 times that available in conventional terrestrial resources. Finding a sustainable way to harvest uranium from seawater will provide a source of nuclear fuel for generations to come, while also giving all countries with ocean access a stable supply. This will also eliminate the need to store spent fuel for potential future reprocessing, thereby addressing nuclear proliferation issues as well. While extraction of uranium from seaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Detailed cost models developed have shown that the primary components of seawater uranium production are adsorbent synthesis and ocean deployment of the adsorbent. Symbiotic deployment strategies have been shown to decrease seawater production costs by 30% [20,19], leaving the adsorbent synthesis as the primary driving factor of cost. With an adsorbent with a uranium uptake of 4.6 g/kg adsorbent, the uranium production cost from a symbiotic deployment scheme was found to be ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed cost models developed have shown that the primary components of seawater uranium production are adsorbent synthesis and ocean deployment of the adsorbent. Symbiotic deployment strategies have been shown to decrease seawater production costs by 30% [20,19], leaving the adsorbent synthesis as the primary driving factor of cost. With an adsorbent with a uranium uptake of 4.6 g/kg adsorbent, the uranium production cost from a symbiotic deployment scheme was found to be ca.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentration of cobalt (Co 2+ ) in seawater is much smaller than other metal ions, both copper (Cu 2+ , with a seawater concentration approximately twice that of Co 2+ ) and uranium ( UO 2 (CO 3 ) 3 4− with a seawater concentration about eight times that of Co 2+ ) have proven extractable, with the latter economically competitive with breeder reactors [19,20].…”
Section: Seawater Sources Of Cobaltmentioning
confidence: 99%
See 1 more Smart Citation
“…This shell enclosure can be incorporated into a Symbiotic Machine for Ocean uRanium Extraction (SMORE) which utilizes adsorbent shells that are incrementally spaced along high strength mooring rope, resembling conventional ball-chain belts. These ball-chains are then strung together to create a net using incrementally spaced cross-members which add rigidity and reduce the likelihood of tangling of individual lengths [6,52,53]. Two versions of this device, shown in figure 8, were tested at a 1/10th physical scale in a nine-week ocean trial, one in which the adsorbent ball-chain net (a) (b) Figure 7: Decoupling of mechanical and chemical requirements via a tough, outer protective sphere encapsulating a soft, inner adsorbent.…”
Section: Symbiotic Design Strategies For Uranium Extraction From Seawmentioning
confidence: 99%
“…Figure 8: Three-dimensional model of 1/10th physical scale model for ocean testing of the SMORE design. Both a stationary and continuous version of the design were fabricated and mounted to a wooden float for ocean testing [6,53].…”
Section: Symbiotic Design Strategies For Uranium Extraction From Seawmentioning
confidence: 99%